De Hegel a Marx: da inflexão ontológica à antítese direta - Sartori, Vitor Bartoletti [UNESP] (Univ Fed Minas Gerais, Dept Filosofia &ciencias Humanas, 2014)
We will deal with the Marxian criticism to the Hegelian notion of "being". it will be shown that historicity and objectivity are determinations of this category (and that categories are always.,forms of being, determinations of existence). So, the analogy between the Hegelian logic and the Marxian theory may sometimes, hide essential aspects of the materialist comprehension of history Here, we intend to prove that, by questioning the treatment dispensed to the matter of being by Hegel, Marx criticizes the Hegelian inversion between subject and predicate in a way that, although dialoguing with Hegel, his conception is the exact opposite at the same time.

Abordaremos a crítica marxiana à noção hegeliana de "ser" (Sein), mostrando que a historicidade e a objetividade, em verdade, são determinações desta (sendo as categorias, em Marx, formas de ser [Daseinsformen], determinações de existência [Existenzbestimmungen]). Deste modo, intentamos mostrar que analogias entre a lógica hegeliana e a teoria marxiana podem eclipsar aspectos centrais à abordagem materialista proposta pelo autor de "O capital". Apontando a inversão hegeliana entre sujeito e predicado, Marx trata da apreensão do real que, muito embora seja traçada em diálogo com a dialética hegeliana, é também sua antítese direta (direktes Gegenteil).
From Hegel to Marx: of the ontological to direct antithesis
Keywords: Marx; Hegel; Being; Objectivity; Marx; Hegel; Ser; Objetividade (Gegenständlichkeit)